Efeito da fixação do polo inferior do baço e da secção da membrana peritoneal gastroesplênica na vitalidade do remanescente da esplenectomia subtotal em ratos - Fernanda Alves Mendonça (2014)
Procedures on the spleen has changed in the last years, and in this scope, indication for total splenectomy has been reduced. Subtotal splenectomy preserving the lower pole is the newest option for preserving spleen parenchyma. Purpose: Verify the viablility of the spleen lower pole after subtotal splenectomy with suture to the stomach and after posterior peritoneal gastroesplenic membrane resection, using macro and microscopic avaliations. Methods: Sixty Wistar rats were used in this study and were randomly distributed in the 3 groups: Group 1: (n=20), subtotal splenectomy with lower pole preservation, Group 2: (n=20) subtotal splenectomy with lower pole preservation and suture to the stomach, Group 3: subtotal splenectomy with lower pole preservationa and posterior peritoneal ligament resection. The animals were sacrificed 45 days after the surgery and the spleen lower poles were removed for macroscopic and microscopic examination. Results: All animals in this series survived. No macroscopic diferences were encountered between the groups. Microscopic avaliation observed statistic diference about fibrosis between group 1 and 3 (p0,05), but no diferences when analysed necrosis or inflamation. Conclusions: Viability of the spleen lower pole after subtotal splenectomy is not modified when its fixed to the stomach or when the posterior peritoneal gastrosplenic ligament is resected.